Dimethylsulfoniopropionate and Methanethiol Are Important Precursors of Methionine and Protein-Sulfur in Marine Bacterioplankton - Kiene, Ronald P. (American Society for Microbiology, 1999)
Organic sulfur compounds are present in all aquatic systems, but their use as sources of sulfur for bacteria is generally not considered important because of the high sulfate concentrations in natural waters. This study investigated whether dimethylsulfoniopropionate (DMSP), an algal osmolyte that is abundant and rapidly cycled in seawater, is used as a source of sulfur by bacterioplankton. Natural populations of bacterioplankton from subtropical and temperate marine waters rapidly incorporated 15 to 40% of the sulfur from tracer-level additions of [(35)S]DMSP into a macromolecule fraction. Tests with proteinase K and chloramphenicol showed that the sulfur from DMSP was incorporated into proteins, and analysis of protein hydrolysis products by high-pressure liquid chromatography showed that methionine was the major labeled amino acid produced from [(35)S]DMSP. Bacterial strains isolated from coastal seawater and belonging to the α-subdivision of the division Proteobacteria incorporated DMSP sulfur into protein only if they were capable of degrading DMSP to methanethiol (MeSH), whereas MeSH was rapidly incorporated into macromolecules by all tested strains and by natural bacterioplankton. These findings indicate that the demethylation/demethiolation pathway of DMSP degradation is important for sulfur assimilation and that MeSH is a key intermediate in the pathway leading to protein sulfur. Incorporation of sulfur from DMSP and MeSH by natural populations was inhibited by nanomolar levels of other reduced sulfur compounds including sulfide, methionine, homocysteine, cysteine, and cystathionine. In addition, propargylglycine and vinylglycine were potent inhibitors of incorporation of sulfur from DMSP and MeSH, suggesting involvement of the enzyme cystathionine γ-synthetase in sulfur assimilation by natural populations. Experiments with [methyl-(3)H]MeSH and [(35)S]MeSH showed that the entire methiol group of MeSH was efficiently incorporated into methionine, a reaction consistent with activity of cystathionine γ-synthetase. Field data from the Gulf of Mexico indicated that natural turnover of DMSP supplied a major fraction of the sulfur required for bacterial growth in surface waters. Our study highlights a remarkable adaptation by marine bacteria: they exploit nanomolar levels of reduced sulfur in apparent preference to sulfate, which is present at 10(6)- to 10(7)-fold higher concentrations.